Impact of Russia-Ukraine War on Sustainable Development Goals: A Study through Indian Financial Market Perspective - Pathak, Smriti; Thakkar, Jalpa; Gurbaxani, Arpita; Virani, Shreya; Thakkar, Prerak (International Journal of Energy Economics and Policy, 2023)
This study measures impact of geopolitical crisis concerning Russia Ukraine War with reference to Sustainable development Goal 8. The researchers have analyzed the variables such as Indian stock market performance, MCX crude oil and Indian GDP Indices to calculate the linear interdependencies among crude oil, Indian stock market performance and Gross Domestic Product using monthly data from January 2016 to May 2022 using a Vector Autoregressive (VAR) model. Time series stationarity is checked using Augmented Dickey-Fuller test. The time series used for the analysis are MCX iCOMDEX crude oil Index, Nifty 50 Index, and GDP Index. Correlation is measured using the Granger Causality Test and VAR model. The outcome demonstrates that the lagged values of the Nifty and crude oil prices indexes are very effectively used to explain the GDP Index. Granger’s Causation Matrix shows that past value of NIFTY Index causes change in GDP Index similarly past value of Nifty Index causes change in MCX Crude oil Index, whereas MCX crude oil does not cause much change in GDP Index. Further research could be done using a detailed time series for a longer period to find any impact of crude oil prices on GDP.